Analysis of village-owned enterprises (BUMDes) welfare: Social capital as moderation - Yustin, Else Meilani; Baroroh, Hilmy (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Proper management of  village-owned enterprises (BUMDes) can be one of the pillars of independence for villages to realize mutual benefit and has multiplier effect for their members. The purpose of this study is to investigate the impact of the performance of BUMDes on the welfare of management and BUMDes members, using social capital as a moderation variables evidence from Sleman Regency. This BUMDes performance measurement uses three components of performance measurement, there are: responsiveness, responsibility, and accountability. Well-being is measured using income variables. The sample size of this study around 11 BUMDes with a total of 50 respondents. This study used quantitative methods with PLS-SEM analysis model and WarpPLS 7.0 analysis tool. These findings reveal that responsiveness, responsibility, and accountability have an impact on the revenues of management and BUMDes members. Meanwhile, the variable of social capital moderation can only strengthen the relationship between the responsiveness of BUMDes to the income of BUMDes management and BUMDes members. The implication of the study  to improve the quality of human resources and the ability to commit to managing BUMDEs as crucial factors to increase BUMDEs performances and lead to an increase in their member's welfare.